EVALUATION OF EX VIVO ANTICATARACT ACTIVITY OF ETHANOLIC EXTRACT OF ALSTONIA SCHOLARIS LEAVES ON DEXAMETHASONE-INDUCED CATARACT BY USING ISOLATED GOAT LENS - Bandaru, Nagaraju; A, Ramu; P, Vijetha; S, Vidhyadhara; P, Nandini; S, Abhilash Reddy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To investigate the ex vivo anticataract activity of ethanolic extract of Alstonia scholaris (EEAS) leaves on dexamethasone-induced cataract using isolated goat lens. Methods: Anticataract activity is done using isolated goat lens. Goat lens was divided into four groups. Group I: Lens was incubated in artificial aqueous humor (normal control). Group II: Lens was incubated with dexamethasone 10 mg (toxic control). Group III and IV: Lens was incubated with dexamethasone and EEAS (50 µg and 100 µg) and subjected to photographic evaluation for opacity; lens was homogenized using Tris-phosphate buffer, and sodium, potassium, total protein, and catalase concentrations were determined. Results: The grades of opacity were 0, 3, 1, and 1 in group I, II, III, and IV, respectively. The present study showed higher total proteins (p<0.05 at all concentration) and K+ ions (p<0.05 at all concentration), whereas lower concentrations of Na+ ions (p<0.05 at all concentration) with EEAS-treated groups. The level of catalase was found to be less in experimentally induced cataract lenses as compared to normal control group. The lenses treated with EEAS showed a significant rise in enzyme level suggesting maintenance of antioxidant enzyme integrity. Conclusion: The present investigation suggests that EEAS leaves effectively prevent the cataractogenic condition. Thus, the goat lens model and dexamethasone-induced cataract model could be used for testing of various anticataract agents. Keywords: Cataract, Artificial aqueous humor, Lens, Dexamethasone, Alstonia scholaris.